Apakah Efek Media Sosial dalam Aktivitas Perdagangan Saham di Indonesia Berlaku pada Jenis Saham? Systematic Literature Review - Risti Herliana; Nugroho Wisnu Murti; Indriyana Widyastuti (Excellent, 2026)
This study synthesizes empirical evidence on the relationship between social media and stock trading activity in Indonesia, examining whether the effect applies uniformly across all stocks or varies by stock characteristics. A Systematic Literature Review (SLR) was conducted using Publish or Perish on Google Scholar with the keywords "Media Sosial" and "Saham," yielding 9 articles after screening. The synthesis reveals three key findings. First, empirical results are inconsistent across studies. Second, no research has specifically examined how stock characteristics, such as market capitalization, liquidity, or industry sector—moderate the relationship; all studies treat stocks homogeneously. Third, the dominant theoretical frameworks are the Theory of Planned Behavior and the Theory of Reasoned Action, yet none incorporate firm characteristics. These findings suggest that social media effects may vary by stock characteristics, though further research is needed to confirm this gap.